2006
DOI: 10.1007/s10822-006-9082-y
|View full text |Cite
|
Sign up to set email alerts
|

GALAHAD: 1. Pharmacophore identification by hypermolecular alignment of ligands in 3D

Abstract: Alignment of multiple ligands based on shared pharmacophoric and pharmacosteric features is a long-recognized challenge in drug discovery and development. This is particularly true when the spatial overlap between structures is incomplete, in which case no good template molecule is likely to exist. Pair-wise rigid ligand alignment based on linear assignment (the LAMDA algorithm) has the potential to address this problem (Richmond et al. in J Mol Graph Model 23:199-209, 2004). Here we present the version of LAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
152
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(159 citation statements)
references
References 21 publications
0
152
0
6
Order By: Relevance
“…GALAHAD aligns molecules and generates pharmacophore hypotheses in the form of hypermolecules incorporating the structural information of the dataset. [32,33] The core computational methodology of GALAHAD is a genetic algorithm that operates on a set of individual models in which each model is defined by a set of torsions for each molecule in the dataset. The pharmacophore is obtained through a procedure whereby the program first identifies corresponding features in ligands paired on the basis of structural similarity, then aligns the conformations in Cartesian space and merges the ligands into a single hypermolecule.…”
Section: Methodsmentioning
confidence: 99%
“…GALAHAD aligns molecules and generates pharmacophore hypotheses in the form of hypermolecules incorporating the structural information of the dataset. [32,33] The core computational methodology of GALAHAD is a genetic algorithm that operates on a set of individual models in which each model is defined by a set of torsions for each molecule in the dataset. The pharmacophore is obtained through a procedure whereby the program first identifies corresponding features in ligands paired on the basis of structural similarity, then aligns the conformations in Cartesian space and merges the ligands into a single hypermolecule.…”
Section: Methodsmentioning
confidence: 99%
“…For ETR, 20 mutations, including V90I, A98G, L100I, K101E/H/P, V106I, E138A/G/K/Q, V179D/ F/T, Y181C/I/V, G190S/A, and M230L, have been identified as resistance-associated mutations (RAMs) (43), while 15 mutations, including K101E/P, E138A/G/K/Q/R, V179L, Y181C/I/V, H221Y, F227C, and M230I/L, have been recognized as RAMs for RPV (26). However, the degree of resistance conferred by each of these mutations can be variable, and studies on recombinant HIV-1 RT enzymes and HIV-1 infectious clones have demonstrated, for example, that the G190A mutation does not affect susceptibility to ETR (53).…”
mentioning
confidence: 99%
“…Our attempts to update the Catalyst models with new data and utilize excluded volumes have been unsuccessful to this point and this could be due to data variability or the inclusion of stereoisomers. We also attempted to use additional 3D-QSAR methods including GALAHAD [47] and a 4D-QSAR method [48] but were also unable to generate a significant model with these software tools, which further indicated the complexity perhaps inherent in this dataset (stereoselectivity and multiple pharmacophores). Our attempts with the pharmacophore software, Phase was partially successful, producing a pharmacophore with 2 hydrogen bonds and 2 hydrophobic areas, using 14 of the 21 training molecules (Fig 3C).…”
Section: Discussionmentioning
confidence: 99%